Outcome and prognostic factors in T4a oropharyngeal carcinoma, including the role of HPV infection - Psychogios, Georgios; Mantsopoulos, Konstantinos; Agaimy, Abbas; Brunner, Kathrin; Mangold, Elisabeth; Zenk, Johannes; Iro, Heinrich (BioMed Research International, 2014)
The prognosis of patients with advanced oropharyngeal carcinoma (OPSCC) is generally poor. The aim of this study is to investigate the different therapeutic approaches and identify prognostic factors associated with a worse outcome for patients treated for T4a OPSCC, in order to improve treatment selection for the individual.A retrospective study was conducted on 426 patients with T4a OPC treated between 1980 and 2010. Eleven prognostic factors including treatment modality, lymph node staging, and p16 status as a surrogate marker for human papillomavirus (HPV) infection were analyzed.Univariate analysis showed a significant difference in DSS between N0 and N+ (57.1% versus 26.9%, P < 0.001), primary surgical and primary nonsurgical treatment (52.7% versus 31.4%, P < 0.001), and perinodal invasion (51.7% versus 19.9%, P = 0.011). P16-negative patients tended towards a worse DSS than p16-positive patients (40.2% versus 64.6%, P = 0.126) but responded better to primary surgery than to nonsurgical treatment (71.4% versus 34.0%, P = 0.113). Multivariate analysis identified the N category as an independent prognostic factor for survival.The survival of p16-negative patients was worse than p16-positive patients, although they seem to respond better to primary surgery. The strongest independent prognostic factor for T4a carcinomas proved to be the presence of lymph node metastases.
EVALuna2:6638